The real SAP® Business One cost: a case study of ERP adoption in an SME. (2013) - Griffiths, Marie; Heinze, Aleksej; Ofoegbu, Anthony
This paper reports on a UK based service management Small and Medium-sized Enterprise (SME) that invested into SAP ® Business One. The action research case study highlights the real cost and difficulties faced in moving to the one single SAP system and the process that was followed in order to identify third-party vendors that can integrate or customise SAP ® Business One. This paper highlights the additional costs required to ensure a 'fit-for-purpose' solution to close the gap between strategic needs and the existing SAP Business One solution. The gap itself is illustrated by highlighting 10 key functionalities expected by the given service management SME. The actual implementation cost of the Enterprise Resource Planning (ERP) was found to be approximately double the initial SAP costs. The real costs involve time for, among other things, process reengineering, strategic decision making, software add-ons, staff-training, project-management and software maintenance.